School-Based Management and Pedagogical Competence as Predictors of Teacher Performance - Ari Yunita; Bukman Lian; Suherman Suherman (Yayasan Sembilan Pemuda Indonesia, 2027)
This study examines the influence of school-based management and teachers’ pedagogical competence on teacher performance in a rural public elementary school context, where systemic support and professional development are often constrained. A quantitative correlational design was employed at SD Negeri 2 Tugumulyo, Belitang Madang Raya District, OKU Timur Regency, South Sumatra. The population comprised 86 teachers from two public elementary schools, with a sample of 44 teachers from SD Negeri 2 Tugumulyo selected through purposive sampling. Data were collected using Likert-scale questionnaires, supported by observation and documentation. Instruments measured school-based management, pedagogical competence, and teacher performance. Analyses included validity and reliability tests, assumption tests, simple regression, and multiple regression using SPSS. School-based management positively and significantly influenced teacher performance (R = 0.806; R² = 0.649; t = 15.142; p < 0.001), as did pedagogical competence (R = 0.875; R² = 0.766; t = 20.159; p < 0.001). Simultaneously, both variables explained 81.2% of the variance in teacher performance (R = 0.901; R² = 0.812; F = 265.744; p < 0.001). This study uniquely integrates school-based management and pedagogical competence as joint predictors of teacher performance within a rural Indonesian elementary setting, an underexplored combination in existing literature. Findings emphasize that school autonomy and participatory management must be accompanied by sustained pedagogical capacity-building to optimize teacher effectiveness. This research contributes empirical evidence that teacher performance is substantially strengthened when institutional autonomy and instructional competence are developed synergistically, offering actionable insights for school leaders and policymakers in similar rural contexts.